Computational Study for some synthesised derivatives of mono and di-[(E) -1-phenylmethylene]-1-cyclohexanone and their biological activities - Arabya A. A. Almutaleb , Boubaker M. Housouna; Huda S. Alrawig (Journal of Pure & Applied Sciences, 2018)
The principal interest in our study is computational study, for a variety of conjugated Ketones such as mono and diarylidene cyclohexanones, using molecular modeling calculation. The molecular modeling study adopted was quantum mechanics calculation using Gaussian 03 software. The quantum mechanics calculations performed using the semi empirical method PM3. The synthesis route had been done through the reactions of some aromatic aldehydes derivatives with cyclohexanone. The mechanism of the formation of the products were discussed. The structure of the synthesized compounds has been confirmed by analytical and spectral methods (IR, 1HNMR and mass spectra) in addition to the elemental analysis (C, H, N). The resulting compounds was applied to the biological activity, which indicates different effects on different kinds of bacteria.